Ginsenoside Rg1 enhances the resistance of hematopoietic stem/progenitor cells to radiation-induced aging in mice - Chen Cui; Mu Xin-yi; Zhou Yue; Shun Ke; Geng Shan; Liu Jun; Wang Jian-wei; Chen Jie; Li Tin-yu; Wang Ya-ping (Acta Pharmacologica Sinica, 2016)
Cui CHEN1, Xin-yi MU1, Yue ZHOU3, Ke SHUN1, Shan GENG1, Jun LIU1, Jian-wei WANG1, Jie CHEN2, Tin-yu LI2, Ya-ping WANG1, * 1Laboratory of Stem Cells and Tissue Engineering, Department of Histology and Embryology, Chongqing Medical University, Chongqing 400016, China; 2Chongqing Stem Cell Therapy Engineering Technical Center, Chongqing 400016, China; 3Department of Histology and Embryology, Dali University, Dali 671000, China Aim: To investigate the effects of ginsenoside Rg1 on the radiation-induced aging of hematopoietic stem/progenitor cells (HSC/HPCs) in mice and the underlying mechanisms. Methods: Male C57BL/6 mice were treated with ginsenoside Rg1 (20 mg·kg-1·d-1, ip) or normal saline (NS) for 7 d, followed by exposure to 6.5 Gy X-ray total body irradiation. A sham-irradiated group was treated with NS but without irradiation. Sca-1+ HSC/HPCs were isolated and purified from their bone marrow using MACS. DNA damage was detected on d 1. The changes of anti-oxidative activities, senescence-related markers senescence-associated β-galactosidase (SA-β-gal) and mixed colony-forming unit (CFU-mix), P16INK4a and P21Cip1/Waf1 expression on d 7, and cell cycle were examined on d 1, d 3, and d 7. Results: The irradiation caused dramatic reduction in the number of Sca-1+ HSC/HPCs on d 1 and the number barely recovered until d 7 compared to the sham-irradiated group. The irradiation significantly decreased SOD activity, increased MDA contents and caused DNA damage in Sca-1+ HSC/HPCs. Moreover, the irradiation significantly increased SA-β-gal staining, reduced CFU-mix forming, increased the expression of P16INK4a and P21Cip1/Waf1 in the core positions of the cellular senescence signaling pathways and caused G1 phase arrest of Sca-1+ HSC/HPCs. Administration of ginsenoside Rg1 caused small, but significant recovery in the number of Sca-1+ HSC/HPCs on d 3 and d 7. Furthermore, ginsenoside Rg1 significantly attenuated all the irradiation-induced changes in Sca-1+ HSC/HPCs, including oxidative stress reaction, DNA damage, senescence-related markers and cellular senescence signaling pathways and cell cycle, etc. Conclusion: Administration of ginsenoside Rg1 enhances the resistance of HSC/HPCs to ionizing radiation-induced senescence in mice by inhibiting the oxidative stress reaction, reducing DNA damage, and regulating the cell cycle. Keywords: ginsenoside Rg1; hematopoietic stem and progenitor cell (HSC/HPC); ionizing radiation; cellular senescence; oxidative stress; DNA damage; cell cycle This study was supported by the National Natural Science Foundation of China, No 81173398, 30973818, 30970872, and 81202785. * To whom correspondence should be addressed. E-mail ypwangcq@aliyun.com Received 2013-05-05 Accepted 2013-08-28